Integrated Timber, Forage and Livestock Production - Benefits of Silvopasture - Jarek Nowak; Ann Blount; Sarah Workman (EDIS)
This document is Circular 1430, one of a series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First Published: December 2002.